\(x^2+6x+15\)
\(=x^2+2\cdot x\cdot3+9+6\)
\(=\left(x+3\right)^2+6\ge6\forall x\)
Dấu "=" xảy ra \(\Leftrightarrow x=-3\)
Đúng 0
Bình luận (0)
Ta có:
x2 + 6x + 15
= x * x + 3x + 3x +15
= x*( x+ 3 ) + 3x +15
= x*( x+ 3 ) + 3x+3*3 + 6
=x*( x+ 3 ) + 3( x + 3 ) + 6
=( x+ 3 ) * ( x+ 3 ) +6
=( x+ 3 )2 +6
Vì ( x+ 3 )2 lớn hơn hoặc = 0 với mọi x
=> ( x+ 3 )2 + 6 lớn hơn hoặc = 6 với mọi x
Dấu " = " xáy ra khi và chỉ khi :
( x+ 3 )2 + 6 = 0
=> ( x+ 3 )2 = -6 ----> Vô lý ( Vì ( x+ 3 )2 + 6 lớn hơn hoặc =0 với mọi x)
Đúng 0
Bình luận (0)